2007
DOI: 10.1080/13548500600568183
|View full text |Cite
|
Sign up to set email alerts
|

The link between judgments of comparative risk and own risk: Further evidence

Abstract: Individuals typically believe that they are less likely than the average person to experience negative events, a phenomenon termed "unrealistic optimism". The direct method of assessing unrealistic optimism employs a question of the form, "Compared with the average person, what is the chance that X will occur to you?". However, it has been proposed that responses to such a question (direct-estimates) are based essentially just on estimates that X will occur to the self (self-estimates). If this is so, any fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 36 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…The selection of measurement method (indirect or direct) clearly influences cross-cultural patterns of unrealistic optimism and pessimism. Some researchers have dismissed comparative biases (e.g., unrealistic optimism) that emerge from the direct method because such measurements are flawed and driven more by cognitive processes (e.g., egocentrism) than motivational tendencies (Aucote & Gold, 2005;Covey & Davies, 2004;Gold, 2007;Hamamura et al, 2007;. It remains controversial, however, as to whether one type of judgment represents the most veridical measure of comparative bias.…”
Section: Appropriateness Of Indirect Versus Direct Methodsmentioning
confidence: 99%
“…The selection of measurement method (indirect or direct) clearly influences cross-cultural patterns of unrealistic optimism and pessimism. Some researchers have dismissed comparative biases (e.g., unrealistic optimism) that emerge from the direct method because such measurements are flawed and driven more by cognitive processes (e.g., egocentrism) than motivational tendencies (Aucote & Gold, 2005;Covey & Davies, 2004;Gold, 2007;Hamamura et al, 2007;. It remains controversial, however, as to whether one type of judgment represents the most veridical measure of comparative bias.…”
Section: Appropriateness Of Indirect Versus Direct Methodsmentioning
confidence: 99%
“…To control for differences in real-life experiences, participants also rated how often these events had happened to themselves or relatives in the past. Results demonstrated that participants reporting no OCD symptoms showed an unrealistic optimism bias (Gold, 2007;Weinstein, 1980). That is, they deemed negative events to happen less likely to themselves as compared to others, and positive events to happen more likely to themselves than others.…”
mentioning
confidence: 89%
“…Third, manipulations of event characteristics, such as to the perceived frequency, desirability, or controllability of an event, produce predictable changes in comparative optimism and pessimism (e.g., Chambers et al., 2003; Gold, 2007; Kruger & Burrus, 2004; see also Kruger, 1999; Reber, Meier, Ruch‐Monachon, & Tiberini, 2006). Although such manipulations should have no overall effect on people's comparative risk estimates because they affect the self and comparison group's chances exactly the same, they do, evidently because people give too little consideration to how the comparison group's chances are affected and too much to how their own are affected.…”
Section: Non‐motivated (Cognitive) Accounts Of False Uniqueness Percementioning
confidence: 99%